Deconstructing Power Relations and Language Asymmetry in the Documentary Pesta Babi: A Critical Pragmatics Analysis - Ismail Marzuki; Wahid Eko Purwanto; Juwilsi Thianci Rawung (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
The documentary film Pesta Babi (2024) documents contemporary colonial practices in South Papua through the National Strategic Project (Proyek Strategis Nasional/PSN) on food and energy, which implicates a network of power encompassing the state apparatus, military, corporations, and religious institutions. This study aims to deconstruct the power relations and language asymmetry operating within the utterance texts of the documentary, employing the framework of Critical Pragmatics. Data were derived from the film's oral transcripts, comprising utterances from state officials, indigenous Papuan communities, corporate representatives, and church leaders. A qualitative method was employed through Critical Pragmatics-based oral discourse analysis. The analysis reveals four dominant patterns: (1) legitimation through institutional euphemisms such as